If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11 = 2x + 33 Reorder the terms: -11 + 3x = 2x + 33 Reorder the terms: -11 + 3x = 33 + 2x Solving -11 + 3x = 33 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -11 + 3x + -2x = 33 + 2x + -2x Combine like terms: 3x + -2x = 1x -11 + 1x = 33 + 2x + -2x Combine like terms: 2x + -2x = 0 -11 + 1x = 33 + 0 -11 + 1x = 33 Add '11' to each side of the equation. -11 + 11 + 1x = 33 + 11 Combine like terms: -11 + 11 = 0 0 + 1x = 33 + 11 1x = 33 + 11 Combine like terms: 33 + 11 = 44 1x = 44 Divide each side by '1'. x = 44 Simplifying x = 44
| 14-b=8 | | -4+3x=7x+x+14x-8x | | 65=-6-x | | 81=x+181 | | 6/10-2/100 | | V-10=-19 | | -4+3x=7x+x+14-8x | | 9a-6=8a+1 | | 2x+2x+x+3x+3=24 | | 2x+0=5y-0 | | 5x+6=9x+3+8x | | 7bf^4-7bk^4= | | 6u(-5u^4)=0 | | 2a-1=3(a+1)+7a+5 | | X+4+5x+3+4x=21 | | (y^-1/4)^1/6 | | 9-3v=0 | | 17x-36=12x+7 | | x+8=-72 | | 2(x-6)=3(x-4) | | y^(3/2)-10y | | 18=x/7 | | 66=1.5x | | -5(6y-6)-y=-3y(y-5) | | 16a^4+36a^3b-10a^2b^2= | | 5(7n-4)-3= | | -0.666+4w=-0.111 | | -7+4(1+5a)= | | 9xa+1=8a | | 2v^2(8v^2+6vb-5b^2)= | | (z^4/16)^3/4 | | (m-3)+5=16 |